Perancangan sistem informasi antrian service motor sebagai pendataan bengkel berbasis Android (Studi kasus : M2 Motor Bogor) - Susanto, Dwi Andrian; Ramayanti, Desi (Institut Agama Islam Negeri (IAIN) Curup, 2021)
M2 Motor Workshop is a workshop in the process of its service in the field of two-wheeled vehicle repair services and the sale of spare parts and other components at M2 Motor Bogor is still carried out manually. The manual process in the M2 workshop is the collection of spare parts stock that is still recorded in the book, the service process to customers, the process of assigning tasks to technicians, and also the workshop owner still receives all transaction reports manually. This study aims to design a motorcycle service queue information system as an android-based workshop data collection which is expected to make it easier for customers to service motorbikes by taking the service queue number first through this application and customers can see service status, service cost data and spare parts data. in real time. Employees or admins can manage payment invoices, customer data, technician data, service data, spare parts data and make monthly reports for workshop owners through the system. Workshop owners can easily find out monthly reports, service data and spare parts data through the system. The research method for developing this system is to use the waterfall model and Unified Modeling Language (UML) to visualize the modeling.